Integrasi Pengujian Peraturan Perundang-Undangan di Mahkamah Konstitusi sebagai Upaya Pembangunan Hukum Indonesia - Nafiatul Munawaroh; Maryam Nur Hidayati (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The first and foremost problem in this study is testing the urgency of the legislation that is integrated in the Constitutional Court. Secondly, it deals with the relevance of the integration testing of the legislation to the development of law in Indonesia. This is a juridical normative research whose legal materials were analyzed descriptively and qualitatively. The study reveals that first, the idea of unification of judicial review of legislation in the Constitutional Court is very essential to do, in order to harmonize the legislation, to maximize the protection of constitutional rights of citizens, and to realize the supremacy of the constitution. Second, the unification of legislation testing can fix elements of the legal system that is particularly an instrument or substance of the law, which highly affect law-making and institutional capacity building, namely the Supreme Court, the Constitutional Court and the executive in Indonesia.